The function given is a composite function. Let's work from the outside in:
![y=(ln(sinh(2x)))](https://tex.z-dn.net/?f=y%3D%28ln%28sinh%282x%29%29%29)
First step:
![\frac{d}{dx}[y]= \frac{d}{dx}[ln(sinh(2x))]](https://tex.z-dn.net/?f=%20%5Cfrac%7Bd%7D%7Bdx%7D%5By%5D%3D%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bln%28sinh%282x%29%29%5D)
Now, let's work it out:
![\frac{dy}{dx} = \frac{1}{sinh(2x) } * \frac{d}{dx}[sinh(2x)]](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B1%7D%7Bsinh%282x%29%20%7D%20%2A%20%20%20%5Cfrac%7Bd%7D%7Bdx%7D%5Bsinh%282x%29%5D)
Next step:
![\frac{dy}{dx} = \frac{1}{sinh(2x) } * cosh(2x) * \frac{d}{dx}[2x]](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B1%7D%7Bsinh%282x%29%20%7D%20%2A%20cosh%282x%29%20%2A%20%20%5Cfrac%7Bd%7D%7Bdx%7D%5B2x%5D%20)
Next step:
![\frac{dy}{dx} = \frac{1}{sinh(2x) } * cosh(2x) *2](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B1%7D%7Bsinh%282x%29%20%7D%20%2A%20cosh%282x%29%20%2A2)
Simplify:
![\frac{dy}{dx} = \frac{2cosh(2x)}{sinh(2x) }](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%20%5Cfrac%7B2cosh%282x%29%7D%7Bsinh%282x%29%20%7D)
Simplify further:
![\frac{dy}{dx} = 2 (\frac{cosh(2x)}{sinh(2x)})](https://tex.z-dn.net/?f=%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%202%20%28%5Cfrac%7Bcosh%282x%29%7D%7Bsinh%282x%29%7D%29)
Remember that:
![{\frac{cosh(x)}{sinh(x)} = coth(x)](https://tex.z-dn.net/?f=%20%7B%5Cfrac%7Bcosh%28x%29%7D%7Bsinh%28x%29%7D%20%3D%20coth%28x%29)
So,
your final answer is:![\boxed{ \frac{dy}{dx} = 2coth(2x) }](https://tex.z-dn.net/?f=%5Cboxed%7B%20%5Cfrac%7Bdy%7D%7Bdx%7D%20%3D%202coth%282x%29%20%7D)
So, your answer is
C. Hope I could help you!
Answer:
(x - 25) / 4
Step-by-step explanation:
In this scenario, we have one unknown variable which is the total of the bag of almonds, therefore we can represent this with the variable x. Since Lorenzo ate 25 of this bag we would need to subtract this from the total of the bag. Then we need to divide the remainder by 4 since each of his friends ate the rest in equal parts. This would leave us with the following expression ...
(x - 25) / 4
Answer:
![\sqrt[3]{3}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B3%7D)
Step-by-step explanation:
We are required to simplify the quotient: ![\dfrac{\sqrt[3]{60} }{\sqrt[3]{20}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csqrt%5B3%5D%7B60%7D%20%7D%7B%5Csqrt%5B3%5D%7B20%7D%7D)
Since the <u>numerator and denominator both have the same root index</u>, we can therefore say:
![\dfrac{\sqrt[3]{60} }{\sqrt[3]{20}} =\sqrt[3]{\dfrac{60} {20}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csqrt%5B3%5D%7B60%7D%20%7D%7B%5Csqrt%5B3%5D%7B20%7D%7D%20%3D%5Csqrt%5B3%5D%7B%5Cdfrac%7B60%7D%20%7B20%7D%7D)
![=\sqrt[3]{3}](https://tex.z-dn.net/?f=%3D%5Csqrt%5B3%5D%7B3%7D)
The simplified form of the given quotient is
.
Answer:
see below
Step-by-step explanation:
1. 0 = (r + 1)(r + 8)
Using Zero Product Property, r = -1, r = -8
2. h(r) = (r + 1)(r + 8)
= r² + 9r + 8
= (r + 9/2)² - 81/4 + 8
= (r + 4.5)² - 12.25 (Complete the square)
Vertex: (-4.5, -12.25)